THE INFLUENCE OF LOCATION AND WORD OF MOUTH PROMOTION ON PURCHASING DECISIONS AT CIPULIR MARKET, SOUTH JAKARTA - Desafitri RB, Linda; Irfal, Irfal; Emier Osman, Ismeth (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This research aims to determine the influence of location and word of mouth promotion on purchasing decisions at the Cipulir market. This research uses a quantitative and qualitative approach by applying multiple regression analysis. Data collection was carried out by distributing questionnaires to respondents who were asked to rate them using a Likert scale of 1 to 5. The population that was the research subject was visitors to Cipulir Market, with a sample size of 100 respondents. Sampling was carried out using the Accidental Sampling method. communication of product value to strengthen their market position. The strategic nature of the Cipulir market influences purchasing decisions with accessibility, product availability, socio-cultural environment and market image. Markets with many sellers and product variations are the main choice for consumers, coupled with a friendly environment and a positive market image. Word of Mouth is also important because of social interaction in traditional markets, where recommendations and reviews from other parties provide strong incentives for potential buyers.